A two-dimensional problem of filtration theory - Ngoc, Dao Minh (Vietnam Journal of Mechanics, 1985)
The problem about free surface of ground Water flow is scaled Completely with considering the convection diffusion of soluble matter and the matter exchange with ground. A local one-dimensional method of changeable directions is used to perform calculations.